2001
DOI: 10.1038/35059104
|View full text |Cite
|
Sign up to set email alerts
|

RGS2 regulates signal transduction in olfactory neurons by attenuating activation of adenylyl cyclase III

Abstract: The heterotrimeric G-protein Gs couples cell-surface receptors to the activation of adenylyl cyclases and cyclic AMP production (reviewed in refs 1, 2). RGS proteins, which act as GTPase-activating proteins (GAPs) for the G-protein alpha-subunits alpha(i) and alpha(q), lack such activity for alpha(s) (refs 3-6). But several RGS proteins inhibit cAMP production by Gs-linked receptors. Here we report that RGS2 reduces cAMP production by odorant-stimulated olfactory epithelium membranes, in which the alpha(s) fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
1
6

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(183 citation statements)
references
References 23 publications
3
173
1
6
Order By: Relevance
“…In this respect, direct binding of RGS2, RGS3, RGS4, and GAIP to phospholipase Cb1 interferes with activated Gaq subunits (Hepler et al, 1997;Anger et al, 2004). Also, RGS2 and RGS 3 interact with adenylyl cyclases reducing cAMP production (Chatterjee et al, 1997;Sinnarajah et al, 2001). The direct association of RGS proteins with the intracellular domains of GPCRs could help to deactivate GaGTP subunits before they regulate their corresponding effectors.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, direct binding of RGS2, RGS3, RGS4, and GAIP to phospholipase Cb1 interferes with activated Gaq subunits (Hepler et al, 1997;Anger et al, 2004). Also, RGS2 and RGS 3 interact with adenylyl cyclases reducing cAMP production (Chatterjee et al, 1997;Sinnarajah et al, 2001). The direct association of RGS proteins with the intracellular domains of GPCRs could help to deactivate GaGTP subunits before they regulate their corresponding effectors.…”
Section: Discussionmentioning
confidence: 99%
“…While RGS2 can act as a GAP protein for Gα i and Gα S proteins (Ingi et al 1998;Sinnarajah et al 2001), it is the most potent RGS for Gαq, the Gα subunit pivotal for the signalling of most vasoconstrictors, including noradrenaline, AngII, endothelin-1, thromboxane, vasopressin and thrombin (Heximer et al 1997). RGS2 will not only attenuate Gαq-mediated vasoconstrictor signals, vasoconstrictors such as AngII can also stimulate RGS2 transcript expression, which will ultimately result in a further feedback inhibition of Gαq-mediated signals (Grant et al 2000).…”
Section: Genetic Variants Of the Regulator Of G Protein Signalling (Rmentioning
confidence: 99%
“…While one report failed to demonstrate an association between the Add1 460W allele and ischemic stroke (Morrison et al 2001), Psaty and co-workers reported an increased risk for combined hemorrhagic and ischemic stroke in carriers of the Add1 460W allele, although there was no association to hypertension itself (Psaty et al 2002). In the same study mentioned just above, Morrison and coworkers (2001) documented an increased frequency for subclinical strokes in carriers of the GNB3 T allele, again independent of an effect on blood pressure.…”
Section: Hypertension and Strokementioning
confidence: 99%
“…These proteins share the conserved ''RGS domain'' of Ϸ120 aa which is responsible for accelerating GTPase activity on the G protein ␣ subunit (4)(5)(6). RGS proteins are thought to play a central role in the physiological regulation of the G protein cycle, and their importance has been confirmed in the immune response (7) and sensory perception (8,9). To date, more than 20 mammalian RGS proteins have been identified.…”
mentioning
confidence: 99%